2000
DOI: 10.1086/315832
|View full text |Cite
|
Sign up to set email alerts
|

IgA Plasma Cell Infiltration of Proximal Respiratory Tract, Pancreas, Kidney, and Coronary Artery in Acute Kawasaki Disease

Abstract: The etiology and pathogenesis of Kawasaki disease (KD) remain unknown. As previously reported, in US patients with acute KD, IgA plasma cells (PCs) infiltrate the vascular wall. To determine whether IgA PCs are increased at mucosal sites in KD and to determine whether other nonvascular KD tissues are infiltrated by IgA PCs, the cells were immunolocalized and quantitated in tissue sections taken from 18 US and Japanese patients who died of acute KD and from 10 age-matched controls. IgA PCs were significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
141
2
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(155 citation statements)
references
References 35 publications
7
141
2
5
Order By: Relevance
“…41 Recent investigations support an alternative hypothesis: The immune response in Kawasaki disease is oligoclonal (antigen driven, ie, similar to a response to a conventional antigen) rather than polyclonal (as found typically in superantigen-driven responses), and immunoglobulin A (IgA) plasma cells play a central role. [42][43][44] It also is possible that Kawasaki disease results from an immunologic response that is triggered by any of several different microbial agents. Support for this hypothesis includes documented infection by different microorganisms in different individual cases, failure to detect a single microbiological or environmental agent after almost 3 decades of study, and analogies to other syndromes caused by multiple agents (eg, aseptic meningitis).…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…41 Recent investigations support an alternative hypothesis: The immune response in Kawasaki disease is oligoclonal (antigen driven, ie, similar to a response to a conventional antigen) rather than polyclonal (as found typically in superantigen-driven responses), and immunoglobulin A (IgA) plasma cells play a central role. [42][43][44] It also is possible that Kawasaki disease results from an immunologic response that is triggered by any of several different microbial agents. Support for this hypothesis includes documented infection by different microorganisms in different individual cases, failure to detect a single microbiological or environmental agent after almost 3 decades of study, and analogies to other syndromes caused by multiple agents (eg, aseptic meningitis).…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…43,45 The prominence of IgA plasma cells in the respiratory tract, which is similar to findings in fatal viral respiratory infections, suggests a respiratory portal of entry of an etiologic agent or agents. 44 Enzymes including matrix metalloproteinases that are capable of damaging arterial wall integrity may be important in the development of aneurysmal dilatation. 46 Vascular endothelial growth factor (VEGF), monocyte chemotactic and activating factor (MCAF or MCP-1), tumor necrosis factor-␣ (TNF-␣), and various interleukins also appear to play important roles in the vasculitic process.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Although progress has been made in defining the genetic influence on KD susceptibility and disease outcome, the complex genetic variants that are responsible have only partially been identified. Based on both the clinical presentation and histopathology of tissues, it has been postulated that the trigger enters through the mucosa of the upper respiratory tract (5). A recent study demonstrated a role for both regional winds and large-scale atmospheric circulation in transporting an etiologic agent responsible for the seasonal and nonseasonal anomalous variation in the number of KD patients in both Japan and the United States (6).…”
mentioning
confidence: 99%
“…It is unknown whether B cells are activated non-specifically by agents such as cytokines, or mitotic substances derived from infectious agents, or specifically by various yet undefined antigens. Oligoclonal IgA plasma cell infiltration occurs in the vascular wall in acute KD patients (36,37). In this study, by using TNFα-treated HUVEC as an inflammatory model of endothelial cells, we showed that the antigens in those cells were recognized by IgG antibodies from KD patients.…”
Section: Discussionmentioning
confidence: 61%